Colonial Trade Policies and The Production of Economic Inequality In Bangalore Between 1800 And 1947 - Sridhara Babu K.R. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
This paper critically examines the colonial trade policies implemented in Bangalore between 1800 and 1947 and their long-term consequences in shaping patterns of economic inequality. The study explores how British economic interests, revenue systems, and trade frameworks systematically restructured Bangalore’s local economy to serve imperial objectives rather than indigenous development. Colonial authorities introduced export-oriented trade mechanisms, prioritising commodities beneficial to the British market while neglecting local consumption and production needs. This redirection of economic activity disrupted traditional trade networks, marginalised native artisans and weavers, and eroded the foundations of indigenous industries that once sustained the regional economy. Drawing on archival materials, including administrative reports, revenue records, and census data, the paper situates Bangalore’s economic transformation within the broader imperial framework of exploitation and dependency. The study argues that British policies such as differential land revenue systems, monopolisation of trade routes, and selective infrastructural investments particularly in railways, cantonments, and commercial zones were instrumental in producing spatial and social inequalities. The historical processes laid the groundwork for enduring disparities in wealth distribution, occupational mobility, and urban infrastructure in postcolonial Bangalore. By revisiting the city’s colonial economic past, this paper contributes to broader debates on the political economy of empire and its persistent legacies in shaping urban inequality in South Asia.